Efficient generation of transgenic mice by lentivirus‐mediated modification of spermatozoa. Issue 2 (2nd December 2013) - Chandrashekran, Anil; Sarkar, Rupa; Thrasher, Adrian; Fraser, Scott E.; Dibb, Nicholas; Casimir, Colin; Winston, Robert; Readhead, Carol
Abstract : Transgenic technologies conventionally rely on the oocyte as a substrate for genetic modification. Owing to their accessibility, however, male germ cells, including mature sperm, have material advantages for use in transgenesis. Here we have exploited lentiviruses to generate transgenic animals via the male germline. When pseudotyped lentiviral vectors encoding green fluorescent protein (GFP) were incubated with mouse spermatozoa, these sperm were highly successful in producing transgenics. Lentivirally transduced mouse spermatozoa were used in in vitro fertilization (IVF) studies, and when followed by embryo transfer, ≥42% of founders were found to be transgenic for GFP. Inverse PCR strategy for integration site analysis demonstrated integration of at least 1 or 2 copies of GFP in the transgenics, mapping to different chromosomes. GFP expression was detected in a wide range of murine tissues, including testis and the transgene was stably transmitted to a third generation of transgenic animals. This relatively simple, yet highly efficient, technique for generating transgenic animals by transducing spermatozoa with lentiviral vectors in vitro is a powerful tool for the study of fertilization/preimplantation development, vertical viral gene transmission, gene function and regulation, and epigenetic inheritance.—Chandrashekran, A., Sarkar, R., Thrasher, A., Fraser, S. E., Dibb, N., Casimir, C., Readhead, C., Winston, R. Efficient generation of transgenic mice by lentivirus‐mediated modification of spermatozoa. FASEB J. 28, 569–576 (2014). www.fasebj.org